Sustainability trade-offs in the circular economy: a maturity-based framework - Ünal, Enes; Sinha, Vikash Kumar (Wiley, 2023)
The theoretical and practical understanding of sustainability implementation has been changing in depth and scope. In particular, circular economy paradigms (e.g., Cradle to Cradle or “C2C” practices) have enabled firms to rethink their resource management behavior, resulting in distinct trade-off patterns among different sustainability dimensions. Furthermore, while many established firms remain reactive and market-oriented in their sustainability implementations, sustainability-rooted firms proactively integrate sustainability practices into their core business. The prior literature on sustainability trade-offs has unduly focused more on established firms that predominantly indulge in market-oriented decisions and trade-offs between profit and sustainability, lacking insights into the approaches adopted by sustainability-rooted firms and trade-offs among the different dimensions of sustainability. We performed a mixed-methods study to address this gap and illustrated the rationale and dynamics of trade-offs among five sustainability dimensions (i.e., material health, material reutilization, renewable energy, water stewardship, and social fairness). We primarily focused on firms in the United States and the European Union since they are the leading areas in terms of circular economy adoption. We explained the pattern of sustainability trade-offs and associated them with a three-stage maturity framework, namely, low-hanging fruits, exploratory, and resource and time intensive. We contributed to the theory by depicting the influence of resource allocation and sustainability maturity level on trade-offs among the five dimensions of sustainability. Practitioners can leverage our framework to better understand their sustainability transformation and make more informed decisions for attaining higher levels of sustainability with more impact.
Keywords: C2C; circular economy; Cradle to Cradle; maturity; mixed methods; sustainability; trade-offs